Breast-feeding Duration: Early Weaning—Do We Sufficiently Consider the Risk Factors?. Issue 5 (November 2015) - Karall, Daniela; Ndayisaba, Jean-Pierre; Heichlinger, Angelika; Kiechl-Kohlendorfer, Ursula; Stojakovic, Sarah; Leitner, Hermann; Scholl-Bürgi, Sabine
ABSTRACT: Objectives: Breast-feeding is the recommended form of nutrition for the first 6 months. This target is unmet, however, in most industrialized regions. We evaluated aspects of breast-feeding in a cohort of mother–baby dyads. Methods: Breast-feeding practices in 555 mother–baby dyads were prospectively studied for 24 months (personal interview at birth and 7 structured telephone interviews). Results: Of the babies, 71.3% were fully breast-fed on discharge from maternity hospitals and 11.9% were partially breast-feed. Median breast-feeding duration was 6.93 (interquartile range 2.57–11.00) months; for full (exclusive) breast-feeding 5.62 (interquartile range 3.12–7.77) months; 61.7% received supplemental feedings during the first days of life. Breast-feeding duration in babies receiving supplemental feedings was significantly shorter (median 5.06 months versus 8.21 months, P  < 0.001). At 6 months, 9.4% of the mothers were exclusively and 39.5% partially breast-feeding. Risk factors for early weaning were early supplemental feedings (odds ratio [OR] 2.87, 95% CI 1.65–4.98), perceived milk insufficiency (OR 7.35, 95% CI 3.59–15.07), low breast-feeding self-efficacy (a mother's self-confidence in her ability to adequately feed her baby) (OR 3.42, 95% CI 1.48–7.94), lower maternal age (OR 3.89, 95% CI 1.45–10.46), and lower education level of the mother (OR 7.30, 95% CI 2.93–18.20). Conclusions: The recommended full breast-feeding duration of the first 6 months of life was not reached. Sociodemographic variables and factors directly related to breast-feeding practices play an important role on breast-feeding duration/weaning in our region. Understanding risk factors will provide insights to give better support to mothers and prevent short- and long-term morbidity following early weaning.